The business and consumption of "American" jeans in Singapore from the 1950s to 1990s - Tan, Danielle Xinyi (Nanyang Technological University, 2024)
This study examines the history of jeans in Singapore from its entrance in the 1950s, up till the end of the twentieth century through socio-cultural, economic and business dimensions. In particular, the consumption of jeans in Singapore was highly shaped by interactions between the flow of foreign socio-cultural ideas, the circulation of jeans and the emergence of a mass consumer culture among an increasingly affluent local population during a period of social, political and economic change. As such, these consumer-commodity relations underscored processes on a global and local scale which transformed a foreign commodity into an identifying marker of the local youth while blurring yet reinforcing categories of class and gender. However, beyond these developments, the production, circulation and consumption of jeans on an international scale within the local business and retail sector underscored the transformation of what was originally an American cultural commodity into a global product. Through a case study of Singapore, this paper aims to fill the lacuna in existing literature on the history of jeans which predominantly consist of works centred on America, Europe and Asia.